(untitled) (International Journal of Innovative Technologies in Economy, 2024)
In the contemporary digital landscape, the rapid proliferation of web applications and frameworks has captivated the focus of cybersecurity professionals. While these modern technologies are crucial for user experience and business operations, this shift in attention often comes at the expense of foundational network protocols—DNS, DHCP, and TCP/IP. These protocols form the bedrock of network security and efficiency. This paper explores the critical role of managing DNS, DHCP, and TCP/IP in maintaining a secure and efficient network infrastructure. By emphasizing the need to balance attention between cutting-edge web technologies and fundamental network protocols, this study highlights the vulnerabilities that arise from neglecting these essential components. Effective management of these protocols is likened to fortifying the basic structures of a country house, ensuring a robust defense against vulnerabilities.